Predicting marital satisfaction on the basis of identity style, Tehran, Iran - Seyed Esmaili, Saeed; Zade Mohammadi, Ali; Hakami, Mohammad (Archives of Men’s Health, 2020)
Introduction: Marital satisfaction affected mental and physical health, life satisfaction, career success, and social communications, and is one the most important indices of life satisfaction. Among all the factors relating to the marriage, the marital adjustment has a special place in the study of marriage and family relationships. Identity development is conceptualized as a process beginning in adolescence and peaking in the early adulthood period during which one explores and commits to possibilities in interpersonal relationship. During this time, young adults are determining the importance of parental, marital, and career life roles. The aim of this study was to determine the relationship between identity styles with marital satisfaction and identification of predicting factors on marital satisfaction centers of city councils of Tehran, Iran. Methods: This was a correlational cross-sectional study. The population includes all couples referring to city councils in the 10th and 11th zones. Participants’ duration of marriage was between 1 and 10 years. In this study, a total of 200 couples were selected using convenience cluster sampling, and the questionnaires were given and distributed to them in health homes, cultural centers of Tehran municipal. Tools of study were Enrich marital satisfaction questionnaire and Identity Style questionnaire. Questionnaires were collected and data were entered in SPSS software ver. 18 and analyzed. Descriptive tests, Pearson correlation test, and Multivariate Regression Test were used for description and analysis of data. Results: The mean age of samples in this study was 31.60 years old with standard deviation of 5.12 years (Ranged between 20- 44 years). Demographic data had normal distribution (P<0.05). One-way ANOVA analysis showed that there was significant relationship between the age of men and marital satisfaction (P= 0.01). Univariate Linear Model showed that there was no significant correlation between literacy (P=0.908) and occupation (P=0.629) with marital satisfaction. There was a significant relationship between marital satisfaction with normative and commitment styles (P<0.05) but there was no significant relation between this and informative and diffuse/avoidant styles (P>0.05). Linear regression analysis showed that only commitment style of identity can predict the marital satisfaction significantly.